Agricultural dust explosions in 2010 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were 11 dust explosions reported in the U.S. in 2010 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 8 in 2009 and a ten-year average of 9.8 explosions per year.
Keywords: Grain dust; Dust explosions